Information and communication - Strauss, Danie (Department of Communication Science, University of the Free State, 2016)
After the Enlightenment of the 18th century concern for the lonesome individual and the need for communication gave birth to the academic disciplines of psychology and communication science. Positivism and the linguistic turn explored the distinction of what is observable and invisible. Information assumed a place alongside matter and energy in the classical formulation of Wiener: “Information is information.” The problem of information and body-plans appears to be a key element in the tradition of vitalism. Rainer Schubert-Soldern identifies form with the “order” of the cell and more recently the ID movement (Intelligent Design) addressed the problem of an increase in information presented by the Cambrian explosion. However, having assumed the current practice of viewing information as an object for natural scientific investigation is radically questioned by Peter Janich when he criticizes this Legend and its icons. The impasse involved in this Legend also entails a challenge to the status of natural laws. Physical laws as conditions for what is physical are not themselves physical in nature. Janich argues that we are inclined to use information in a metaphorical sense as if it is a natural scientific object of investigation. Alternatively one should commence with communication between more than one human actor because it is only within such a communicative context that one actor can inform another actor and that information becomes meaningful. Schuurman is therefore correct when he asserts that at bottom information is lingual.
Keywords: Information; Communication; Natural scientific object; Metaphor; Naturalising prejudice; Physicalism; Body-plan; Cambrian explosion; The lingual nature of information